Peran pinjaman online dalam meningkatkan inklusi keuangan generasi digital indonesia - Auliya, Isnaeni Nur (Maliki Interdisciplinary Journal, 2025)
The development of financial technology (fintech) in Indonesia has created significant opportunities to enhance financial inclusion, particularly through online lending services. This research analyzes the role of online lending as a financial inclusion instrument for Indonesia's digital generation, comprising millennials and Gen Z. Online lending platforms offer easy access, rapid approval processes, and more flexible requirements compared to conventional banking. These digital platforms successfully reach previously unbanked and underbanked population segments, especially tech-savvy younger generations. However, challenges including low financial literacy, evolving regulations, and unethical debt collection practices remain significant concerns. The analysis reveals that online lending has substantial potential to drive financial inclusion, but requires a comprehensive approach involving financial education, regulatory improvements, and responsible business practices to maximize benefits and minimize risks for Indonesia's digital generation. The integration of technology with financial services through online lending represents a crucial step toward achieving broader financial inclusion goals in Indonesia's rapidly digitalizing economy.